Implementasi Pemikiran Harun Nasution dalam Dunia Pendidikan Islam - Sahrawi (Al-Ishlah: Jurnal Pendidikan Islam, 2022)
This article wants to show Harun Nasution's ideas in Islamic education whose role is not only related to the concept level, but also real implementation by changing the curriculum and methods of Islamic education, being able to develop a critical, rational, and open attitude, especially in Islamic studies. So that what is being done is to build an integral Islamic education, which integrates various disciplines of science, reason, and revelation. Education must be carried out continuously in order to create educational harmony for students while maintaining a religious attitude and open-mindedness.